Pemutusan Hubungan Kerja Lokal Dipekerjakan Oleh Perwakilan Negara Asing Di Indonesia - Ferinda Khairunissa Fachri; Fitria Fitria; Diana Mutia Habibaty (JOURNAL of LEGAL RESEARCH, 2022)
This thesis focuses on employment termination conflicts between Indonesians and FCRs. Foreign Country Representatives argued that the Indonesia Industrial Relations Court lacks the authority to decide a quo issue since it has diplomatic and state immunity. This study uses normative legal approach and international and domestic law as sources. The 1961 Vienna Convention and the 1963 Vienna Convention, the International Labor Organization's Termination of Employment Convention 1982, and the United Nations Convention on Jurisdictional Immunities of States and Their Property 2005 are the primary sources of international law, while Indonesia's national laws are the Code of Civil Law, Act Number 2 of 2004 on Settlement of Industrial Relations (PPHI), Act Number 11 of 2020 on Job Creation, and a few others. The research also reviews three court decisions on Foreign Country Representatives' termination of employment with Indonesians and compares them to the aforementioned laws. This study found that terminated local employees can sue in Industrial Relations Court. Due to the defendants being foreign state representatives, the case must also comply with the employees' and Foreign Country representations' agreement (e.g. Embassy, Consulate). The Agreement between the two nations controls the Industrial Relations Court's authority in disputes involving Indonesian (local) workers and foreign country representations in Indonesia, as well as court judgements.